Dynamic heterogeneous analysis of pollution reduction in SANEM countries: Lessons from the energy-investment interaction - Peter Ekundayo Mesagan; Kazeem Bello Ajide; Xuan Vinh Vo (African Governance and Development Institute (AGDI), 2021)
This scientific enquiry examines the role of capital investment in the energy-pollution model in SANEM countries. The methodology is based on the Pooled Mean Group (PMG), which is appropriate for a heterogeneous panel. Findings reveal that energy use negatively impacts CO2 emissions in Algeria, South Africa, Morocco, and the panel, in the short-run; however, it positively impacts CO2pollution in Nigeria, Egypt, and the panel, in the long-run. Again, investment exerts a positive effect on CO2 in South Africa and Algeria, whereas it is negative in Nigeria, Egypt, and Morocco. Capital investment also expands short-run pollution in the panel, but it reduces long-run pollution. Lastly, the energy-investment interaction reduces the panel's CO2pollution in the short-run and long-run, as well as, in Morocco, Egypt, Nigeria, and South Africa, except in Algeria. Thus, we conclude that capital investment is crucial in the energy-pollution nexus and suggest cooperation in attracting low-carbon emitting investments to the region.
Keywords: Q32; Q48; Q53; F23; O55; 330; Capital Investment; Carbon Emissions; Energy Use; Energy Policy; Africa